A CASE STUDY AND ANALYSIS OF GARMENT RETAILING WITH CONSUMER BEHAVIOR - Dubey, Manish; Saini, Siddharth; Umekar, Srishti (International Journal of Research -GRANTHAALAYAH, 2016)
These are testified through the escalating figure of the garment market is also by the growing tally of fashion brands and retailers whose has occupied substantial share of the country’s retail space. The apparel industry reflects people’s lifestyles and shows their social and economic status. The apparel industry is India’s second largest industry after the IT industry. Young consumer group have gained significant importance from marketers in recent years because of their purchasing power.